b - Payne, V. Gregory; Isaacs, Larry D. (b, 2020)
"Human Motor Development: A Lifespan Approach was first published in 1987. Motor development, the book's main focus, is the study of changes in human movement across the lifespan. This book has been a leader, if not the leading book, in this field across those three decades. It has been continuously updated with the preparation of the 9th edition being the most significant and large-scale revision to date. It is largely intended for an undergraduate motor development course, but can be adapted for graduate use. Motor development is a course that is generally a major requirement in departments of kinesiology (including physical education, exercise science, etc.), the study of human movement, as well as pre-physical therapy and physical therapy programs. Kinesiology is one of the fastest growing fields in higher education. In the California State University system, for example, it is one of the ten largest majors with many of the 23 CSU campuses administering kinesiology departments with well over 1,000 major students. Unique aspects of our book include a more wholistic approach than other books on the market. We emphasize the importance of intellectual, social, and physical development and their impact on human motor development at all ages. Similarly, we examine the effect of motor development on all other aspects of development. In addition, throughout the history of our book, users have consistently praised the readability of our book, especially for the undergraduate student. This is gratifying as this was one of our primary goals when we originally wrote the book. We have remained steadfast in that goal and will be conscientious of that in the preparation of the 10e"--
Includes bibliographical references and index.
Keywords: Motor ability in children; Physical fitness for children